2001
DOI: 10.1001/archotol.127.9.1140
|View full text |Cite
|
Sign up to set email alerts
|

Treating the Elusive Keloid

Abstract: Hypothesis: Surgical excision with a scalpel, primary closure, followed by local steroid injection is the best treatment for a keloid. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These lesions occur after a variety of cutaneous injuries, including surgery, 2 burns, 3 dermal trauma, 4 and acne, 5 and some even arise spontaneously 6 . Keloids and HS can cause physical disfigurement, restricted range of motion, bothersome symptoms, and psychological problems, and yet there is no consensus in the literature regarding appropriate therapy 7–9 . Several treatment modalities, such as intralesional (IL) injections of corticosteroids 10,11 or 5‐fluorouracil, 12 surgical excision, 13 cryotherapy, 14 radiotherapy, 15 pressure therapy, 16 silicone gel sheeting, 17 and laser treatment, 18 have been used with variable success.…”
Section: Introductionmentioning
confidence: 99%
“…These lesions occur after a variety of cutaneous injuries, including surgery, 2 burns, 3 dermal trauma, 4 and acne, 5 and some even arise spontaneously 6 . Keloids and HS can cause physical disfigurement, restricted range of motion, bothersome symptoms, and psychological problems, and yet there is no consensus in the literature regarding appropriate therapy 7–9 . Several treatment modalities, such as intralesional (IL) injections of corticosteroids 10,11 or 5‐fluorouracil, 12 surgical excision, 13 cryotherapy, 14 radiotherapy, 15 pressure therapy, 16 silicone gel sheeting, 17 and laser treatment, 18 have been used with variable success.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, many clinically guided treatments for keloid scar removal exist while the preference of one treatment over the other is generally dictated by the clinical experience of the surgeon. Simple surgical excision and postoperative steroidal injection are the most common forms of keloid treatment 3 . Of these, intralesional steroidal injection with triamcinolone remains the most widely used treatment with an efficacy of over 80% according to early studies; although recurrence is still observed 4,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Simple surgical excision and postoperative steroidal injection are the most common forms of keloid treatment. 3 Of these, intralesional steroidal injection with triamcinolone remains the most widely used treatment with an efficacy of over 80% according to early studies; although recurrence is still observed. 4,29 Intralesional steroidal injections are believed to inhibit fibroblast proliferation and collagen synthesis, and increase collagenase production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations